PENERAPAN TEKNIK KONTRASTIF DALAM MENULIS TEGAK BERSAMBUNG PADA SISWA KELAS 1 SEKOLAH DASAR KABUPATEN MADIUN - Samsiyah, Nur (Universitas Negeri Surabaya, 2018)
ABSTRACTBased on the observation in the classroom, upright writing skillsis less desirable for students. This is known in the implementation of writing the value of students is still low and many are still less tidy or not in accordance with the spelling. This research attempts to apply contrastive techniques in upright writing skills. The formulation of the problem, namely: (1) how is the activity of writing writing upright with the application of contrastive techniques to the students of grade 1 elementary school in Madiun Regency ?; And (2) how the students' learning outcomes in writing upright with the implementation of the technique of contrastive. in grade 1 elementary school students in Madiun Regency? The purpose of this research is to describe the activity and the result of learning to write upright with continuous technique. This research is a qualitative research to know the application of contrastive technique in learning writing. The research data is the 1st grader of SD in Madiun Regency. The method used to collect data in the form of observation and test. Keywords: contrastive technique, upright writing skills